Use of waste materials in highway construction - Ahmed, Imtiaz (Noyes Data Corp., 1993)
This book outlines the state-of-the-practice in the use of waste materials in highway construction in the U.S. and discusses the applications of selected waste materials including: Waste tiresWaste glassReclaimed paving materialsSlags and ashesBuilding rubbleSewage sludgeIncinerator residueAn evaluation based on technical, environmental, and economic factors indicated that reclaimed paving materials, coal fly ash, blast furnace slag, bottom ash, boiler slag, steel slag, and rubber tires have significant potential to replace conventional materials for various applications in highway construction, and should be projected for future construction. Specific applications of the waste products and potential problems associated with their usage in highway operations are also included.